English for the underserved: Closing the digital divide - Michael Carrier (Peoples' Friendship University of Russia (RUDN University), 2018)
This paper explores the problems faced by schools in developing economies worldwide in accessing interactive communications technologies (ICTs) due to lack of electricity, lack of equipment and lack of training both for teachers and for students. Although the middle class in developing economies is growing fast, something like 4 billion members of the global population have no access to digital technology, giving rise to the term, 'digital divide'. Governments, international agencies and charities are all investing personnel and resources to overcome these problems and provide opportunities for language learning and other skills. The paper argues that the introduction of edtech facilities in local schools in emerging economies will help solve problems of overcrowded classrooms and teach learners essential skills that they will need in their careers. It provides case studies from different countries and examines types of educational technology resources and teacher training approaches used to help learners access and master digital literacy.